Blood lactate and lactate tolerance levels of futsal and football players - Yücel Ocak; Sebiha G. Başpınar; Mehmet Yıldız; Mustafa Furkan Ocak (Instituto Brasileiro de Pesquisa e Ensino em Fisiologia do Exercício, 2022)
The aim of this study is to determine futsal and football players' lactic acid levels, lactic acid tolerance and lactic acid content during recovery after maximal strength testing. Study sample consists of 80 voluntary male students (40 football and 40 futsal players) from different universities. The maximal heart rate was achieved during the Yo-Yo test in order to determine participants' running distances. After loading, participants' lactic acid levels were measured right at the end of the test and three minutes after the test. The running distance of futsal players was 1976 meters while that of football players was 2046 meters in the Yo-Yo test. Futsal and football players had a mean lactic acid concentration of 16.277 mmol/l and 14.512 mmol/l, respectively, right after the Yo-Yo test. Futsal and football players had a mean lactic acid concentration of 7.875 mmol/l and 7.705 mmol/l mmol/l, respectively, three minutes after the Yo-Yo test. Football players had a longer running distance than futsal players. Futsal players reached higher lactic acid concentrations and showed more tolerance to lactic acid than did football players during maximal strength testing. Futsal players recovered and removed lactic acid from their bodies faster than football players.